Technology-Assisted Project-Based Language Learning on Wetland Concern - Rina Listia; Yusuf Al Arief; Dzahabiyah Alfia Zahra; Kimilia Azzahra; Rizky Amelia (English Department of Faculty of Tarbiyah and Teacher Training, 2022)
In the midst of independent learning, the implementation of project-based learning method is inseparable. By employing a quasi-experimental study involving English Department students in an experimental class and a control class, this study investigated the effectiveness of Technology-Assisted Project-Based Language Learning with wetland-based concern. The data was collected from the presentation project score and a questionnaire given to the students. The collected data was then analyzed by using Mann-Whitney test and descriptive statistics. Focusing on the two-fold foci, the results showed significant result where the students in the experimental class performed better than those in the control class. Collaboration, motivation, authenticity and students’ mastery to the technology that is Storyjumper impacted to the significant result in this study as confirmed in the questionnaire results. Students perceived positively to the implementation of technology-assisted project based language learning in wetland concern. The result of this research study is expected to be used in teaching and learning in the field of learning English as a foreign language and to encourage students to apply technological innovations in the field of learning English in a wetland environment.